Ferrocene decorated unusual mercury(ii) dithiocarbamate coordination polymers: crystallographic and computational studies. Issue 12 (9th March 2021) - Singh, Amita; Singh, Ayushi; Singh, Suryabhan; Kociok-Köhn, Gabriele; Muddassir, Mohd.; Kumar, Abhinav
Abstract : Three new ferrocene decorated 1D coordination polymers of Hg(ii ) dithiocarbamates were synthesized and the nature of their weak interactions was addressed using computational techniques. Abstract : Three new one dimensional ferrocene decorated Hg(ii ) based coordination polymers with the general formula of (FcCH2 N(C2 H4 OH)NCS2 HgX) n {X = Cl (FcHgCl ); Br (FcHgBr ); I (FcHgI )} have been synthesized using a functionalized dithiocarbamate ligand with a redox active ferrocene pendant and –C2 H4 OH and have been characterized by microanalyses, FTIR, 1 H, 13 C, and 199 Hg NMR, electronic absorption and photoluminescence spectroscopy. The redox properties of these compounds have been assessed by cyclic voltammtery which suggested their quasi-reversible redox behaviour. Single crystal X-ray diffraction studies suggested that the geometries around all three Hg(ii ) polymers are square pyramidal and two such square-pyramids fuse in an antiparallel mode in FcHgCl and FcHgI and in an orthogonal mode in FcHgBr to generate a ferrocene decorated 1D polymeric framework. The adjacent 1D polymeric chains in all three compounds are held by different intermolecular interactions which provide stability to these compounds in the solid state. Also, these compounds exhibit interesting Hg⋯X (X = Cl, Br and I) spodium bonding interactions. The nature of all these interactions have been studied by Hirshfeld surface analyses, density functional theory and quantum theory of atoms in molecules (QTAIM). The QTAIM results indicated that Hg⋯X interactions are moderately strong with interaction energies of 9.32, 44.37 and 19.56 kJ mol −1 for chloro, bromo and iodo derivatives, respectively. Further bond order calculations also suggest the presence of spodium bonding interaction in all three polymers.